HUBUNGAN PENGGUNAAN MEDIA SOSIAL TIKTOK DENGAN KECERDASAN EMOSIONAL SISWA KELAS VI SD NEGERI KERTAUNGARAN - Dani Hamdani; Dadang Cunandar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to determine the relationship between social media tiktok and the emotional intelligence of class VI students at SDN Kertaungaran and determine the level of use of Tiktok and their emotional intelligence. It’s hoped hat benefits of this research can contribute to further research and provide information to teachers, parents, and students regarding the relationship between TikTok and emotional intelligence and its consequences, both positive and negative. This research was motivated by the existence of one the sixth grade students at SDN Kertaungaran who had difficulty controlling his emotions when playing tiktok because his parents ordered him to. The population and sample of this study was class VI as many as 81 people. This type of research uses descriptive quantitative methods with a survey research design. The main data collection technique is by questionnaire. The data collection intruments was a questionnaire with a likert scale . Data analys techniques using normality tests, linearity tests, and correlation tests. The results of this study show that there is a significant relationship between the use of TikTok and emotional intelligence. Proven by a significance value of 0.007 < 0.05. So it can be concluded that there is a positive relationship between the variable use of TikTok social media and emotional intelligence. The results of the Pearson product moment correlation obtained a value of 0.296. This shows that the relationship between the variable use of social media TikTok and the emotional intelligence of SDN Kertaungaran students is at a low level.